Information System and IoT-Based Personnel Location Tracking Through Smart Card Validation: Telekomunikasi Militer - Afriyadi; Gatut Yulisusianto; Juanda Rahimatullah (Pustaka Poltekad, 2026)
This research aims to design and build a web-based system for generating and managing membership cards integrated with Quick Response Code (QR Code) technology at the Army Polytechnic (Poltekad). The system was developed using the Python programming language with the Flask framework and MySQL database, following the Waterfall development method. System testing was conducted using Black Box Testing to verify functionality. The research results show that the system can perform Create, Read, Update, and Delete (CRUD) operations on member data, generate unique QR Codes automatically for each member based on their Registration Number (NRP), print digital membership cards in PDF/Image format integrating profile photos, personal data, and QR Codes, and verify membership through QR Code scanning. The system architecture uses a client-server model with three main entities: users, activity_logs, and kta_templates. Black Box Testing results show that all system functions work according to specifications. This system implementation contributes to the modernization of personnel administration at Poltekad by replacing manual recording methods with an efficient and accurate digital system.